Analisis Keselamatan Dan Kesehatan Kerja Serta Disiplin Kerja Terhadap Kinerja Karyawan - Tika Trisnawati; Soni Kurniawan (Universitas PGRI Yogyakarta, 2021)
The purpose of this research is to test the influence of k3 and discipline of the performance of employees work. Variable in this research is K3 and discipline work as the independent variable, while the performance of employees as dependent variable. Population in this study some 40 people. Analysis using analysis of multiple regression. The testing of hypotheses using analysis test hypotheses with the help of 25 SPSS program version. The research results show that the variable K3 it has some positive effects and significant impact on employee performance, discipline and significant impact on work it has some positive effects of employee performance. K3 and discipline work of a work as simultaneous have had a positive impact and significant impact on employee performance. Variable K3 have leverage against the most dominant of employee performance.